Calcineurin Activates Cytoglobin Transcription in Hypoxic Myocytes - Singh, Sarvjeet (American Society for Biochemistry and Molecular Biology, 2009)
Cardiac hypertrophy develops in response to a variety of cardiovascular stresses and results in activation of numerous signaling cascades and proteins. In the present study, we demonstrate that cytoglobin is a stress-responsive hemoprotein in the hypoxia-induced hypertrophic myocardium and it is transcriptionally regulated by calcineurin-dependent transcription factors. The cytoglobin transcript level is abundantly expressed in the adult heart and in response to hypoxia cytoglobin expression is markedly up-regulated within the hypoxia-induced hypertrophic heart. To define the molecular mechanism resulting in the induction of cytoglobin, we undertook a transcriptional analysis of the 5′ upstream regulatory region of the cytoglobin gene. Evolutionarily conserved binding elements for transcription factors HIF-1, AP-1, and NFAT are located within the upstream region of the cytoglobin gene. Transcriptional assays demonstrated that calcineurin activity modulates cytoglobin transcription. Increased calcineurin activity enhances the ability of NFAT and AP-1 to bind to the putative cytoglobin promoter, especially under hypoxic conditions. In addition, inhibition of calcineurin, NFAT, and/or AP-1 activities decreases endogenous cytoglobin transcript and protein levels. Thus, the regulation of cytoglobin transcription by calcineurin-dependent transcription factors suggests that cytoglobin may have a functional role in calcium-dependent events accompanying cardiac remodeling.